Komparasi Paduan Ethanol dan Dietyl Ether (DEE) pada Gasoline Terhadap Performa Spark Ignition (SI) Engine - Firman Lukman Sanjaya; Faqih Fatkhurrozak; Nur Aidi Ariyanto; Sigit Setijo Budi; Andre Budhi Hendrawan; Syarifudin (Infotekmesin, 2026)
The limited availability of fossil fuels and the growing demand for energy have led to a global energy crisis. Ethanol and DEE can be used as alternative energy to replace fossil fuels. Ethanol and DEE have high RON and oxygen content, as well as low viscosity, which accelerates the flame, thereby increasing torque and SI engine power. DEE is still rarely used as a gasoline blend, but its chemical characteristics can improve engine combustion. This study aims to compare the use of gasoline-ethanol and gasoline-DEE blends on SI engine performance. The test results prove that the DEE15 blend produces the highest torque value of 4.37 N.m or an increase of 28% compared to pure gasoline. The E15 blend produces the highest SI engine torque value of 4.31 N.m or an increase of 26% compared to pure gasoline. In addition, SI engine power increases by 28% in DEE15 and 26% in E15 compared to pure gasoline. From these test results, the use of a gasoline-DEE blend can improve SI engine performance better than gasoline-ethanol.